Effect of Nb doping on the microstructure and superconducting properties of FeSe. (August 2019) - Ma, Qingshuang; Li, Xinhua; Ma, Zongqing; Yu, Liming; Li, Huijun
Abstract: We reported the enhanced superconducting performance of Nb doped FeSe prepared by solid-state sintering. With the increase of Nb doping, Nb incorporated FeSe lattice and substituted Fe sites. Thus the texture of tetragonal FeSe become more compact, the superconducting transition temperature is distinctly enhanced up to 13.6 K in FeNb0.04 Se, which is enhanced by 27% as compared with that of undoped FeSe, and the upper critical field is enhanced up to 28 T. Moreover, Nb doping can significantly suppress the decay of critical current density with magnetic fields, and then improve the transport performance of FeSe at high magnetic fields. Graphical abstract: Unlabelled Image